USAHA MIKRO, KECIL DAN MENENGAH (UMKM) INDONESIA DALAM MENGHADAPI PERDAGANGAN BEBAS DI ASEAN - Elisabeth Pudyastiwi; Agoes Djatmiko (Universitas Pendidikan Ganesha, 2020)
With the enactment of the ASEAN Single Market in 2015 opened opportunities for Indonesian MSMEs to market their products and compete with foreign products. UMKM which is the driving force of the national economy must be able to take this golden opportunity for Indonesia's national interests and not on the contrary we are the market for other member countries. Of course this becomes a challenge for national MSMEs to face the ASEAN Single Market next year, MSMEs must maintain and enhance competitiveness as a creative and innovative industry. In addition, MSMEs must also improve product standards, design and quality to comply with ASEAN regulations by looking at the ISO 26000 requirements for Green Products. The Indonesian government must work hard to help MSMEs who experience obstacles such as facilitating the provision of credit access at banks, providing entrepreneurial training, increasing access to finance for MSMEs, facilitating financing for beginner entrepreneurs. Expanding access to finance and reducing KUR interest costs, Food and Energy security loans, and mapping the potential export of MSME products to ASEAN and other countries and facilitating promotion of MSME products at home and abroad.